Combined airway and oesophageal stenting in malignant airway-oesophageal fistulas: a prospective study - Herth, Felix; Peter, S.; Baty, F.; Eberhardt, Ralf; Leuppi, J. D.; Chhajed, P. N. (The European respiratory journal, 2010)
Malignant airway-oesophageal fistulas (AEF) are a serious complication of advance oesophageal or lung cancer. - The aim of this study was to assess the quality of life before and after stent insertion, and to examine the role of treatment and location of AEF as factors influencing survival in AEF patients managed with airway and/or oesophageal stent insertion. - 112 patients with AEF were included prospectively. 83 (74%) patients had advanced lung cancer and 29 (26%) patients had oesophageal cancers. - Airway stents were inserted in 65 (58%) patients, oesophageal stents in 37 (33%) patients, and both airway and oesophageal stents in 10 (9%) patients. Seven (6%) patients developed respiratory failure and required transient ventilator support in the intensive care unit (four patients with airway stenting, two patients with double stents and one patient in the oesophageal stenting group). None of the patients developed stent migration or needed stent repositioning. Overall, mean survival was 236.6 days (airway stent 219.1 days, oesophageal stent 262.8 days and combined airway-oesophageal stent 252.9 days). Backward, stepwise regression revealed the site of stent placement (airway and/or oesophagus; p<0.028), exact location of the fistula in airway (p = 0.011) and additional treatment with chemotherapy and/or radiation (p<0.001) as independent risk factors predicting increased survival. The mean quality of life score (QoL) was 81 prior to stent insertion and 72 post-stent insertion (p<0.001). - Airway and/or oesophageal stent insertion provides an effective approach to improve the QoL in patients with malignant AEF.